Glass items
By placing a specific composition of SiOC layer, TCO layer and shielding layer on the glass substrate, the problem of peeling or cracking of glass items after forming at high temperature is solved, and excellent heat resistance is achieved.
Patent Information
- Application Number
- CN202180054031.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-04
- Filing Date
- 2021-08-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-08-19
AI Technical Summary
Glass items formed at high temperatures are prone to peeling or cracking of the base layer or shielding layer, and these phenomena may occur within a period of time after forming.
By placing a carbon-silicon oxide layer (SiOC layer), a transparent conductive oxide layer (TCO layer) and a shielding layer on the glass substrate, and the composition ratio (C/Si) of carbon to silicon in the SiOC layer is 0.1 or more and 0.5 or less, the linear expansion coefficient (αsh) of the shielding layer is 7.7×10-3/K or less.
It effectively suppresses peeling or cracking of each layer on the glass substrate after forming at high temperature, and improves the heat resistance of glass items.
Smart Images

Figure CN116096592B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a glass article, in particular to a glass article for a vehicle. Background Art
[0002] Glass articles, such as window glass for vehicles or buildings, are provided with desired properties by coating the surface of a glass substrate with various materials depending on the application.
[0003] Patent Document 1 discloses a glass article for a vehicle in which a base layer, a transparent conductive oxide layer, and a peripheral masking band (masking layer) to which a black pigment or the like is applied are arranged on a glass substrate.
[0004] Generally, a base layer (e.g., SnO2 layer) formed on a glass substrate can function as an alkali diffusion prevention layer to prevent alkali metal ions such as sodium ions from migrating from the glass substrate to the layer on the surface side. It is known to use a carbon-added silicon oxide layer (hereinafter also referred to as "SiOC layer") having excellent alkali diffusion prevention function as a base layer to replace the conventional SnO2 layer and other base layers.
[0005] It is known that a transparent conductive oxide layer (eg, a doped tin oxide layer) has Low-E (Low Emissivity) performance that can reduce radiant heat from sunlight, and can improve the thermal insulation and heat insulating properties of glass articles.
[0006] In addition, a shielding layer is generally provided at the peripheral edge of a glass article for a vehicle (for example, a window glass for an automobile) for the purpose of preventing the adhesive from being degraded by sunlight, improving the appearance, and the like.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application No. 2019-533630 Summary of the invention
[0010] Technical problem to be solved by the invention
[0011] When the glass article of the structure described in Patent Document 1 is formed at a high temperature (e.g., 600° C. or higher) depending on the intended use, each layer (e.g., base layer or shielding layer) disposed on the glass substrate may peel off or crack. Furthermore, even if these phenomena are not observed immediately after the glass article is formed at a high temperature, these phenomena may occur after a certain period of time.
[0012] The present invention has been made to solve the above-mentioned technical problems, and an object thereof is to provide a glass article having excellent heat resistance in which the occurrence of peeling or cracking of each layer arranged on a glass substrate can be suppressed even after a long period of time has passed since being formed at a high temperature.
[0013] Solutions to technical problems
[0014] The present invention provides a glass article having the following structures [1] to [9].
[0015] [1] A glass article comprising a carbon-added silicon oxide layer, a transparent conductive oxide layer and a shielding layer in this order on a glass substrate, wherein the carbon-added silicon oxide layer has an atomic composition ratio of carbon to silicon (C / Si) of not less than 0.1 and not more than 0.5, and the shielding layer has a linear expansion coefficient α sh At 7.7×10 -3 / K or less.
[0016] [2] The glass article as described in [1], wherein the shielding layer contains a crystalline component and a pigment, and the crystallinity value represented by the CPS ratio of the crystalline component to the pigment in X-ray diffraction measurement data of the shielding layer is greater than 7 and less than 33.
[0017] [3] A glass article as described in [1] or [2], wherein the shielding layer contains a crystalline component and a pigment, and the ratio of the C / Si of the carbon-added silicon oxide layer to the crystallinity value represented by the CPS ratio of the crystalline component to the pigment in X-ray diffraction measurement data of the shielding layer is greater than 0.005 and less than 0.04.
[0018] [4] The glass article according to any one of [1] to [3], wherein the linear expansion coefficient α of the carbon-added silicon oxide layer is Si At 0.6×10 -6 / K or above and 4.0×10 -6 / K or less.
[0019] [5] The glass article according to [4], wherein the linear expansion coefficient α of the carbon-added silicon oxide layer is Si In 2.9×10 -6 / K or less.
[0020] [6] The glass article according to any one of [1] to [5], wherein the thickness t of the glass substrate is g It is not less than 2.0 mm and not more than 3.5 mm.
[0021] [7] The glass article according to any one of [1] to [6], wherein the thickness of the carbon-added silicon oxide layer is Si It is greater than or equal to 30 nm and less than or equal to 150 nm.
[0022] [8] The glass article according to any one of [1] to [7], wherein the transparent conductive oxide layer includes at least one of a fluorine-doped tin oxide layer and an antimony-doped tin oxide layer.
[0023] [9] The glass article according to any one of [1] to [8], which is used as a window glass for an automobile.
[0024] Effects of the Invention
[0025] According to the present invention, it is possible to provide a glass article having excellent heat resistance in which the occurrence of peeling or cracking of each layer disposed on a glass substrate is suppressed even after a long period of time has passed since molding at a high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1A is a schematic cross-sectional view of one embodiment of the glass article of the present invention.
[0027] Figure 1B 1 is a schematic top view of one embodiment of the glass article of the present invention.
[0028] Figure 2A It is a schematic cross-sectional view for explaining one embodiment of the glass article of the present invention, and is a schematic cross-sectional view showing a case where the transparent conductive oxide layer is composed of one layer.
[0029] Figure 2B This is a cross-sectional view adapted to explain one embodiment of the glass article of the present invention, and is a schematic cross-sectional view showing a case where the transparent conductive oxide layer is composed of two layers. DETAILED DESCRIPTION
[0030] In the present specification, "to" indicating a numerical range means a range including the numerical values described before and after it as the lower limit and the upper limit.
[0031] In the following, the SiOC layer only means that the layer contains silicon atoms (Si), oxygen atoms (O) and carbon atoms (C), and does not mean that the composition ratio of these atoms (elements) is 1:1:1.
[0032] As described above, when the glass article having the structure described in Patent Document 1 is formed at a high temperature, there is a case where the layers arranged on the glass substrate, for example, the interface between the glass substrate and the base layer, may peel off or crack. Moreover, even if these phenomena are not observed immediately after forming, they may occur after a certain period of time. Furthermore, when the glass article is used as a glass article for a vehicle, in addition to the central part of the glass substrate, cracks or layer peeling may sometimes be observed at the edge of the peripheral part of the glass substrate where the shielding layer is provided. In particular, when a SiOC layer having an excellent alkali diffusion prevention function is used as the base layer, this tendency is particularly obvious.
[0033] The present inventors presume that the peeling or cracking occurs during the heat forming (and subsequent cooling as needed) operation or after a certain period of time due to the low adhesion between the glass substrate and the base layer and the shrinkage force of the shielding layer.
[0034] In particular, when a SiOC layer is used as the base layer, it is estimated that SiOC may be thermally decomposed during molding at high temperatures, thereby further reducing the adhesion between the glass substrate and the base layer, causing peeling or cracking.
[0035] The inventors conducted various studies based on these assumptions. As a result, they found that by making the composition ratio of carbon to silicon C / Si (at% ratio) in the SiOC layer within a specific range and thereby making the linear expansion coefficient of the shielding layer below a specific value, it is possible to suppress the occurrence of these peeling or cracking during heat forming or after a certain period of time, thereby completing the present invention.
[0036] Hereinafter, an embodiment of the glass article of the present invention (hereinafter also referred to as “the present glass article”) will be described in detail with reference to the drawings, but the present invention is not limited to this embodiment.
[0037] <Glass Items>
[0038] The present glass article can be suitable for use as vehicle glass, especially automobile window glass, for automobiles, etc., and can be used for any position of the front, rear, side, and top of the vehicle body. In addition, the present glass article can also be used without restriction in purposes other than vehicles, such as buildings, etc. In addition, the present glass article can be used as a single glass including one glass substrate, or as a laminated glass including multiple glass substrates, as long as it has the following structure on at least a part thereof. The manufacturing method of the present glass article is not particularly limited, and can be manufactured by, for example, a conventionally known float process as described later.
[0039] This glass item is Figure 1A As shown in FIG. 1 , a carbon-added silicon oxide layer (SiOC layer) 2, a transparent conductive oxide (TCO: Transparent Conductive Oxide) layer (hereinafter also referred to as "TCO layer") 3 and a shielding layer 4 are sequentially provided on a glass substrate 1. As described above, these layers may be sequentially stacked on at least a portion of one surface of the glass substrate, and these layers may or may not be stacked on the entire glass substrate constituting the glass article. For example, a SiOC layer 2 and a TCO layer 3 may be sequentially arranged on the entire glass substrate, and then a shielding layer 4 may be sequentially arranged on the entire glass substrate. Figure 1BAs shown in FIG. 1 , a frame-shaped shielding layer 4 is arranged on the TCO layer at the peripheral position of the glass substrate. In addition, other layers, such as a color adjustment layer for adjusting the color tone, may be provided between the layers within the scope of obtaining the effect of the present invention. However, from the perspective of heat resistance, the present glass article is preferably composed of a glass substrate 1, a SiOC layer 2, a TCO layer 3 and a shielding layer 4. Figure 1A and Figure 1B are schematic diagrams of an embodiment of the glass article, Figure 1A A schematic cross-sectional view thereof is shown. Figure 1B A schematic plan view thereof when viewed from the shielding layer 4 side is shown.
[0040] In the glass article, the composition ratio (C / Si) expressed as the ratio of the atomic composition percentage (at%) of carbon to silicon in the SiOC layer, that is, C (at%) / Si (at%) of the SiOC layer is greater than or equal to 0.1 and less than or equal to 0.5. Furthermore, the linear expansion coefficient (thermal expansion coefficient) α of the shielding layer is Sh At 7.7×10 -3 / K or less.
[0041] The glass article having a SiOC layer having a specific C / Si ratio and a shielding layer having a specific linear expansion coefficient has excellent heat resistance, excellent adhesion between the glass substrate and the base layer, and can suppress the occurrence of peeling or cracking caused by the shrinkage force of the shielding layer. Therefore, even when the glass article is formed into a curved shape for a vehicle at a high temperature (e.g., 600 to 750° C.), the occurrence of peeling or cracking of the layers on the glass substrate can be easily avoided.
[0042] [Glass substrate]
[0043] As the glass substrate (glass plate), a conventionally known glass substrate may be used appropriately, for example, heat absorbing glass, transparent glass, soda-lime glass, green glass, UV green glass, etc. may be used. However, when the glass article is used as a vehicle glass, the glass substrate is required to have a visible light transmittance that meets the safety standards of the country where the vehicle is used, and is required to have the characteristics necessary for the application when used for other purposes. Therefore, the glass substrate preferably adjusts the composition appropriately to achieve the desired characteristics. As the composition of the glass substrate, the following composition may be cited. In addition, the composition of the glass substrate may be determined by fluorescent X-ray analysis.
[0044] SiO2: 70-73% by mass
[0045] Al2O3: 0.6-2.4% by mass
[0046] CaO: 7-12 mass%
[0047] MgO: 1.0-4.5% by mass
[0048] R2O: 13-15 mass% (R is an alkali metal such as Na or K)
[0049] Total iron oxide converted to Fe2O3 (T-Fe2O3): 0 to 0.14 mass %.
[0050] The glass substrate may be substantially transparent or may be tinted, ie, colored.
[0051] The shape of the glass substrate is not particularly limited as long as it can be formed into a shape corresponding to the desired use, and can be, for example, rectangular. The shaped shape of the glass article can be a curved shape, and the curved shape is not particularly limited, for example, it can be made into a Figure 1A The glass article includes any one of an article before the glass substrate provided with the SiOC layer, the TCO layer and the shielding layer is formed, and an article after the glass substrate is formed into a desired shape. Therefore, the glass substrate of the glass article may be a glass substrate before forming, for example, a rectangular shape, or a glass substrate after forming, for example, a curved shape.
[0052] Thickness of glass substrate t g There are no particular limitations, but the thickness is preferably 1.0 mm or more, more preferably 1.5 mm or more, and further preferably 2.0 mm or more. g Preferably, it is 6.0 mm or less, more preferably 5.0 mm or less, and further preferably 3.5 mm or less. From the perspective of suppressing layer peeling and cracking, the thickness of the glass substrate is usually preferably about 4.0 to 5.0 mm. However, since the glass article has excellent heat resistance, it can be used even at a thinner thickness than usual, for example, the thickness of the glass substrate is t g When the thickness is 2.0 to 3.5 mm, the glass article can be easily formed, and the degradation or peeling of each layer on the glass substrate can be suppressed when the glass article is formed at a high temperature. Therefore, the glass article can be used not only as a single glass but also as a laminated glass and can be used for various purposes.
[0053] Linear expansion coefficient of glass substrate α g The thickness can be appropriately set by changing the composition, but from the viewpoint of suppressing the peeling of the base layer (SiOC layer) during thermal molding, 0.6×10 -6 / K~10×10 -6 / K. From the same perspective, α g More preferably, 1.0×10 -6 / K~7.0×10 -6 / K, more preferably 1.0×10 -6 / K~4.0×10 -6 / K. At this time, from the perspective of preventing layer peeling, the linear expansion coefficient α of the glass substrate is g It is preferably set so that the linear expansion coefficient α of the base layer at the molding temperature (for example, 600 to 750° C.) is equal to Si The difference is smaller. g It can be measured by the method described later.
[0054] The glass substrate can be appropriately manufactured by a conventionally known method (eg, a float method, a fusion method, and a roll method), and the manufacturing method is not particularly limited. In addition, a commercially available product can also be used as the glass substrate.
[0055] [SiOC layer]
[0056] In the present glass article, a carbon-added silicon oxide layer: SiOC layer (SiOC film) is used as a base layer disposed between the glass substrate and the TCO layer. The method of laminating the SiOC layer on the glass substrate is not particularly limited, but preferably online coating is used to form a film in the manufacturing process of the glass article, and more specifically, online CVD (chemical vapor deposition: chemical vapor deposition) is preferably used.
[0057] The SiOC layer has a superior alkali diffusion prevention function compared to conventional base layers such as a SnO 2 layer, and is excellent in durability and void defect suppression, and is therefore preferably used.
[0058] In the present glass article, the SiOC layer may be disposed on at least a portion of one surface of the glass substrate. Therefore, the SiOC layer may be in contact with the glass substrate, or other layers may be disposed between the glass substrate and the SiOC layer without the glass substrate and the SiOC layer being in direct contact. However, from the perspective of inhibiting layer peeling and cracking, the other layers disposed between the glass substrate and the SiOC layer preferably have a linear expansion coefficient close to that of the glass substrate or the SiOC layer (a layer with a small difference between the two).
[0059] In the present glass article, the composition ratio (C / Si) of carbon atoms (C) and silicon atoms (Si) in the above-mentioned SiOC layer is greater than 0.1 and less than 0.5. When the composition ratio is greater than 0.1, the alkali diffusion prevention function of the SiOC layer can be made more excellent. When the composition ratio is less than 0.5, the heat resistance of the SiOC layer can be improved, and the thermal decomposition of SiOC during the heat forming of the present glass article (for example, high temperature: above 600°C) can be prevented to generate CO2 gas. As a result, the present glass article can be formed at high temperatures and can be used for a variety of purposes, including automotive window glass. From the perspective of maintaining the alkali diffusion prevention function of the SiOC layer, the C / Si in the SiOC layer is preferably greater than 0.15, and more preferably greater than 0.25. From the perspective of the heat resistance of the SiOC layer, the C / Si in the SiOC layer is preferably less than 0.40, and more preferably less than 0.30.
[0060] The at% ratio (O / Si) of oxygen atoms (O) to silicon atoms (Si) in the SiOC layer is not particularly limited, but is preferably 1.2 or more, more preferably 1.5 or more, from the perspective of heat resistance. In addition, from the perspective of maintaining the alkali diffusion prevention function, O / Si is preferably 3.0 or less, more preferably 2.5 or less.
[0061] The atomic composition percentage of oxygen atoms (O) in the SiOC layer is preferably 45 at% or more, more preferably 50 at% or more, and further preferably 55 at% or more. When the at% of oxygen atoms is above these lower limits, the heat resistance of the SiOC layer can be further improved. In addition, the at% of oxygen atoms in the SiOC layer is preferably 70 at% or less, more preferably 65 at% or less, and further preferably 62 at% or less. When the at% of oxygen atoms is below these upper limits, the SiOC layer can be easily endowed with an excellent alkali diffusion prevention function.
[0062] The atomic composition percentage of carbon atoms (C) in the SiOC layer is preferably 2 at% or more, more preferably 3 at% or more, and further preferably 4 at% or more. In addition, the carbon atomic at% of the SiOC layer is preferably 20 at% or less, more preferably 15 at% or less, and further preferably 10 at% or less. When the carbon atomic at% is above these lower limits, the SiOC layer can be easily endowed with an excellent alkali diffusion prevention function. When the carbon atomic at% is below these upper limits, the heat resistance of the SiOC layer can be further improved.
[0063] The atomic composition percentage of silicon atoms (Si) in the SiOC layer is preferably 20 at% or more, more preferably 23 at% or more, and further preferably 25 at% or more. In addition, the silicon atomic at% of the SiOC layer is preferably 35 at% or less, more preferably 34 at% or less, and further preferably 32 at% or less. When the silicon atomic at% is above these lower limits, the heat resistance and alkali diffusion prevention function of the SiOC layer can be further improved. When the silicon atomic at% is below these upper limits, the SiOC layer can be easily endowed with excellent heat resistance and alkali diffusion prevention function.
[0064] In addition, the SiOC layer may contain atoms such as Na, Ca, etc. in addition to the above-mentioned O, C, and Si atoms. From the perspective of providing the glass article with excellent heat resistance and alkali diffusion prevention function, the total at% of O, C, and Si atoms in the SiOC layer is preferably 85 to 99 at%, and more preferably 90 to 98 at%.
[0065] The composition of the SiOC layer can be appropriately adjusted by changing the supply conditions of the raw material gas (mixed gas) during CVD. For example, the composition of the SiOC layer can be adjusted by increasing or decreasing the oxidation degree of the raw material gas (e.g., CO2 / SiH4, CO2 / C2H4), in other words, by increasing or decreasing the supply amount of CO2 gas used as the raw material gas. In addition, the atomic composition of the SiOC layer can be measured by the method described below.
[0066] Linear expansion coefficient of SiOC layer α Si Preferably 0.6×10 -6 / K or more, more preferably 0.8×10 -6 / K or more, more preferably 1.0×10 -6 / K or more. α of SiOC layer Si When the SiOC layer α is greater than these lower limits, it is easy to impart excellent alkali diffusion prevention function to the base layer. Si 4.0×10 is preferred -6 / K or less, more preferably 3.5×10 -6 / K or less, more preferably 3.0×10 -6 / K or less, particularly preferably 2.9×10 -6 / K or less. In addition, the SiOC layer α Si When the content is below these upper limits, the heat resistance of the SiOC layer can be further improved, and the adhesion between the glass substrate and the base layer can be further improved.
[0067] In addition, by properly adjusting the C / Si or O / Si in the SiOC layer, the α Si α of SiOC layer Si It can be measured by the method described later.
[0068] The thickness of the SiOC layer t Si It can be set appropriately without particular limitation, but from the viewpoint of achieving both heat resistance and alkali diffusion prevention function, it is preferably 30 nm or more, more preferably 35 nm or more, and further preferably 40 nm or more. In addition, from the viewpoint of smoothness, the thickness t of the SiOC layer is preferably 100 nm or more. Si It is preferably 150 nm or less, more preferably 120 nm or less, and further preferably 100 nm or less.
[0069] 〔TCO layer〕
[0070] It is known that the transparent conductive oxide layer (TCO layer) used in the present glass article has excellent Low-E performance as described above, and may include, for example, doped tin oxide and doped zinc oxide, and mixtures of two or more thereof. In addition, the TCO layer may also include alkali metal (e.g., potassium, sodium, lithium, etc.) stannate, zinc stannate, cadmium stannate, and mixtures of two or more thereof.
[0071] Among them, from the perspective of having excellent Low-E performance, the TCO layer is preferably a doped tin oxide layer. From the same perspective, the TCO layer is more preferably at least one of a fluorine-doped tin oxide (F: SnOx) layer and an antimony-doped tin oxide (Sb: SnOx) layer. In addition, their oxidation degree (x: for example, 2) can be adjusted by appropriately changing the film forming conditions, such as CVD film forming conditions, without particular limitation.
[0072] The TCO layer can be Figure 2A As shown in FIG. 1 , the glass article has a structure of one TCO layer 3 composed of a F:SnOx layer. The glass article having such a structure of one TCO layer can have a visible light transmittance Tv of 80% or more (e.g., 83%) according to ISO9050 and JIS-R3106. The glass article having such a TCO layer has a high Tv and can be used as a front part or front side part of a car body, specifically a windshield or a window glass beside a driver's seat or a front passenger seat.
[0073] The TCO layer can also be Figure 1A or Figure 2B As shown in FIG. 1 , the glass article has a structure of a multilayer structure of two or more layers including a Sb:SnOx layer as a first TCO layer 3a and a F:SnOx layer as a second TCO layer 3b. The glass article having such a structure of a TCO layer consisting of two or more layers can have a Tv of 25% or less (e.g., 18%). The glass article having a TCO layer of such a structure can be used as a window glass for the rear side, top, or rear of an automobile because of its low Tv.
[0074] Figure 2A and Figure 2Bare schematic cross-sectional views for illustrating one embodiment of the glass article, Figure 2A and Figure 2B The cases where the TCO layer consists of one layer and two layers are shown respectively. Figure 2A and Figure 2B In the figure, the record of the shielding layer is omitted.
[0075] The thickness of the TCO layer is not particularly limited, but from the perspective of providing excellent Low-E performance, the total thickness t TCO The thickness of the SnOx layer is preferably 50 to 700 nm, more preferably 100 to 650 nm. From the same perspective, the thickness of the F:SnOx layer is preferably 100 to 500 nm, more preferably 150 to 350 nm. Furthermore, from the same perspective, the thickness of the Sb:SnOx layer is preferably 250 to 500 nm, more preferably 300 to 450 nm.
[0076] The method of stacking the TCO layer on the SiOC layer is not particularly limited. It is preferred to use online coating in the manufacturing process of the glass article, and more specifically, online CVD is preferred. In addition, in the present glass article, the TCO layer can be arranged on at least a portion of the SiOC layer. Therefore, the TCO layer (in the case of a multi-layer structure, the TCO layer closest to the glass substrate side) can be in contact with the SiOC layer, or other layers can be arranged between the SiOC layer and the TCO layer without the SiOC layer and the TCO layer being directly in contact. However, from the perspective of suppressing layer peeling and cracking, the other layers arranged between the SiOC layer and the TCO layer preferably use layers whose linear expansion coefficients are close to the linear expansion coefficients of the SiOC layer or the TCO layer.
[0077] Linear expansion coefficient of TCO layer α TCO It can be appropriately set without particular limitation, but from the perspective of suppressing the peeling of each layer on the glass substrate, it is preferably the α Si The difference is small, for example, the following range is preferred. That is, the layer α of TCO TCO Preferably 1.0×10 -6 / K or above and 9.0×10 -6 / K or less, the glass article can be used, for example, with a linear expansion coefficient of α TCO 4.0×10 -6 When the TCO layer is composed of multiple layers, all of the multiple TCO layers may satisfy the above-mentioned linear expansion coefficient range, but it is preferred that at least the linear expansion coefficient of the TCO layer closest to the glass substrate side, that is, the SiOC layer side, among the multiple TCO layers is within the above-mentioned range. TCO It can be measured by the method described later.
[0078] [Occlusion layer]
[0079] The shielding layer may be disposed on at least a portion of one surface of the glass substrate, specifically, on at least a portion of the TCO layer, but when the glass article is used as a glass article for a vehicle, it is preferably disposed so as to cover the peripheral edge of the glass substrate. The shielding layer prevents the terminals of the mounting components or electrical components mounted on the vehicle body from being seen from outside the vehicle.
[0080] The shielding layer may be in various shapes such as a frame shape, a strip shape, or a dot shape. Figure 1B In the embodiment, a frame-shaped shielding layer 4 is provided on the periphery of the glass substrate, more specifically, on the periphery of the TCO layer 3. The shielding layer may be provided, for example, in a manner of covering a specific area from the edge of the glass substrate. More specifically, the shielding layer may cover a portion at least within 30 mm from the edge of the glass substrate (for example, within 50 mm from the edge).
[0081] The shielding layer includes a crystalline component and a pigment, and the crystallinity value represented by the diffraction intensity: CPS (counts per second) ratio of the crystalline component to the pigment in the X-ray diffraction measurement data of the shielding layer is preferably greater than 7 and less than 33. The crystalline component of the shielding layer can provide favorable non-adhesion in the compression-bending molding operation performed in the automotive glass industry, and can impart excellent demolding properties. In addition, regarding the above-mentioned crystalline component, the crystal morphology (crystal structure) when it exists in the shielding layer may be different from or the same as the crystal morphology when measured by the above-mentioned XRD.
[0082] If the crystallinity value of the shielding layer, i.e., CPS of the crystalline component / CPS of the pigment, is greater than 7, the crystallinity is further improved, the surface unevenness of the shielding layer becomes larger, and the demolding property during molding can be further improved. From the same perspective, the crystallinity value of the shielding layer is more preferably greater than 10, and particularly preferably greater than 11. When the crystallinity value of the shielding layer is less than 33, it is easy to suppress the layer peeling on the glass substrate when molding glass objects at high temperatures. From the same perspective, the crystallinity value of the shielding layer is more preferably less than 20, and particularly preferably less than 15 (for example, less than 14). In addition, when the shielding layer contains multiple crystalline components or pigments, the CPS of the above-mentioned crystalline component and the CPS of the pigment are respectively calculated using the total value of the CPS of the multiple types to calculate the above-mentioned crystallinity value.
[0083] Here, the crystallinity value of the shielding layer can be adjusted by changing the raw materials (crystalline components or pigments) used for the shielding layer or the firing conditions when firing the shielding layer. As firing conditions, examples include: the firing speed (conveying speed) (mm / s) and firing temperature (°C) when conveying the processed object (which has been given the shielding layer forming material) in the automotive glass forming process, the temperature curve when the firing temperature is changed during firing, etc. Specifically, the crystallinity value can be increased by slowing down the firing speed of the shielding layer or increasing the firing temperature. Conversely, the crystallinity value can be reduced by speeding up the firing speed of the shielding layer or reducing the firing temperature. The firing conditions of the shielding layer can be appropriately set, for example, the firing speed can be 5 to 30 mm / s (preferably 10 to 25 mm / s), and the firing temperature can be 550 to 730°C (preferably 580 to 710°C, more preferably 680 to 710°C). Table 1 below shows an example of the relationship between the crystallinity value of the shielding layer and the firing speed and firing temperature of the shielding layer.
[0084] Table 1 Crystallinity values of shielding layer
[0085]
[0086] The shielding layer (eg, black ceramic layer) can be formed by applying a shielding layer forming material (ceramic paste) on a glass substrate, more specifically, on a desired position (eg, on the peripheral portion) on a TCO layer, and heating and sintering the resultant material at a high temperature.
[0087] The shielding layer forming material before firing contains at least glass material (equivalent to the crystalline component when forming the shielding layer) and a pigment (e.g., a heat-resistant black pigment). In addition, it may contain an (organic) carrier for dispersing the pigment, a conductive metal, a reducing agent, a dispersing surfactant, a fluidity regulator, a fluidity aid, an adhesion promoter, a stabilizer, a colorant, etc. as needed. In addition, as a shielding layer forming material, a commercial product may also be used. As a commercial product of a shielding layer forming material, the trade name: 14501 (manufactured by Ferro Co., Ltd.) can be cited.
[0088] The glass material may include, for example, one or more (solid) crystalline substances such as zinc borate, zinc silicate, aluminum silicate, zinc titanate, and bismuth silicate. In addition, the glass material may also include one or more components such as SiO2, Bi2O3, Cs2O, Na2O, B2O3, ZnO, TiO2, La2O3, Nb2O5, MnO2, CeO2, MoO3, WO3, F, Al2O3, BaO, etc. The glass material may be in the linear expansion coefficient α of the shielding layer. sh The glass frit having a high melting point range is known to have excellent chemical resistance and a relatively low thermal expansion coefficient.
[0089] When forming the shielding layer, the glass material may or may not have a different crystal form from that of the raw material stage (shielding layer forming material) before firing. In addition, the crystalline component in the shielding layer may be composed of one type of glass material, or may be composed of multiple types of glass materials, for example, by firing and fusion. In the examples described below, Bi4(SiO4)3 was observed as the above-mentioned crystal component in the X-ray diffraction measurement data.
[0090] Glass frit can be produced by a conventionally known method. For example, starting materials corresponding to the desired composition are mixed, melted at a desired temperature and time, and cooled with water or the like as required, thereby producing glass frit having the desired composition. Glass frit can be crushed into a desired particle size (e.g., 1 to 8 μm) using a known crushing technique as required. Alternatively, commercially available glass frit can be used.
[0091] The content of glass frit in the shielding layer forming material can be appropriately set within the range that satisfies the above-mentioned crystallinity value after firing. However, from the perspective of easily adjusting the crystallinity value of the shielding layer, the content of glass frit is preferably 60 to 99% by mass, more preferably 65 to 95% by mass, and further preferably 70 to 85% by mass.
[0092] As the above-mentioned pigment, it is possible to appropriately use pigments known in the past, for example, it is possible to use more than one pigment derived from composite inorganic pigments such as corundum-hematite, olivine, ruby, pyrochlore, rutile, spinel, etc. As pigment, it is possible to use metal oxide pigments (spinel pigments) such as copper (Cu), chromium (Cr), iron (Fe), cobalt (Co), nickel (Ni), manganese (Mn), aluminum (Al), magnesium (Mg), zinc (Zn), zirconium (Zr), niobium (Nb), yttrium (Y), tungsten (W), antimony (Sb) and calcium (Ca) etc. These black spinel pigments can be appropriately used in the automotive industry, and in other industries such as construction, household appliances and beverage industries, it is possible to appropriately use other metal oxide pigments producing other colors as pigments.
[0093] Furthermore, the spinel structure is a conventional pigment structure having the general formula AB2X4, wherein X is usually an O with approximately the same ionic radius. 2- or F - Here, A and B represent the tetrahedral and octahedral positions in the standard spinel lattice. The spinel structure can be formed from many different elements including the first row transition elements, forming the structure of many inorganic pigments. Most spinel compounds have a cubic space group, but distorted spinel structures can be tetragonal and sometimes orthorhombic.
[0094] More specific examples of metal oxide pigments include CuO·CrO3, CuCr2O4, (Co, Fe)(Fe, Cr)2O4, MnCr2O4, NiMnCrFe, CuCrMnO, and pigments obtained by modifying these pigments using a modifier. Here, the performance of the pigment can be determined by the raw materials, synthesis technology and conditions, and post-firing treatment. The pigment can be synthesized by a conventionally known method, such as the method described in Japanese Patent Publication No. 2019-509959, or a commercially available product can be purchased, but its composition should be adjusted to the α value of the shielding layer. sh below the specified value.
[0095] The pigment can be formed by, for example, compounding or calcining a minute metal oxide or salt containing the desired metal. In this case, the size of the minute metal oxide can be appropriately set, but is preferably 1 nm to 10 μm, more preferably 10 nm to 1 μm, and further preferably 50 to 500 nm.
[0096] Furthermore, as a pigment, a pigment derived from a rare earth manganese oxide pigment can also be used. For example, (YxMn)Oy, (LaxMn)Oy, (CexMn)Oy, (PrxMn)Oy, and (NdxMn)Oy can be used. Here, in the above chemical formula, x is preferably 0.01 to 99, more preferably 0.08 to 12, and further preferably 0.25 to 4. In addition, in the above chemical formula, y is the number of oxygen atoms required to maintain electrical neutrality, preferably x+1 to 2x+2. As the pigment, specific examples include CeMnO3, PrMnO3, NdMnO3, and pigments obtained by modifying these pigments with a modifier. In addition, the rare earth manganese oxide pigment preferably has a chalcanthite crystal structure or an orthorhombic crystal structure. By using a rare earth manganese oxide pigment, a high infrared reflectivity can be obtained, which can reduce the heating characteristics. Furthermore, the pigment does not contain cobalt materials, and hexavalent chromium will not be generated or dissolved even in acidic solutions such as acid rain.
[0097] The content of the pigment in the shielding layer forming material can be appropriately set within the range that satisfies the above-mentioned crystallinity value after firing. However, from the perspective of easily adjusting the crystallinity value of the shielding layer, the content of the pigment is preferably 0.1 to 50% by mass, more preferably 1 to 25% by mass, and further preferably 2 to 25% by mass.
[0098] Examples of the organic carrier for dispersing and suspending the above materials and pigments include vegetable oils, mineral oils, low molecular weight petroleum fractions, tridecanol, synthetic resins and natural resins.
[0099] As the conductive metal, for example, silver (silver particles) can be used.
[0100] As the reducing agent, for example, silicon metal can be used.
[0101] The dispersing surfactant plays a role in assisting the wetting of the pigment when using an inert particulate inorganic pigment. The dispersing surfactant usually contains a block copolymer having a group having an affinity for the pigment, and further contains a solvent (e.g., xylene, butyl acetate, methoxypropyl acetate) as required. The dispersing surfactant can appropriately use a conventionally known surfactant, for example, Disperbyk 162 (trade name, manufactured by BykChemie) can be used.
[0102] The fluidity modifier is used to adjust the viscosity, and a conventionally known fluidity modifier can be appropriately used. For example, Viscobyk series (manufactured by BYK-Chemie GmbH) can be used.
[0103] The flowability aid is an additive for adjusting viscosity and flowability, and a conventionally known flowability aid can be appropriately used. For example, Additol VXW6388 (trade name, manufactured by UCB Surface Speciality) can be used.
[0104] The adhesion promoter is used to improve compatibility with the layer (TCO layer) provided with the shielding layer, and can be appropriately selected according to the composition of the TCO layer used.
[0105] As the stabilizer, for example, a light stabilizer or a UV blocker can be used.
[0106] The amounts of these additives added can be appropriately set and are not particularly limited.
[0107] Linear expansion coefficient of shielding layer α sh At 7.7×10 -3 / K or less. α of shielding layer sh If the value is below this value, the peeling force caused by the shrinkage of the shielding layer during high-temperature forming and cooling can be easily suppressed, and the layer can be easily prevented from peeling off from the glass substrate. sh More preferably 7.5×10 -3 / K or less. α of shielding layer sh The smaller the better, but the smaller the difference in linear expansion coefficient with the TCO layer disposed under the shielding layer, the more preferred. sh It can be measured by the method described later.
[0108] The ratio of the C / Si of the SiOC layer to the crystallinity value of the shielding layer {(C / Si of the SiOC layer) / (crystallinity value of the shielding layer)} is preferably 0.005 or more and 0.04 or less. When the ratio is 0.04 or less, both excellent mold release during molding and excellent heat resistance of the SiOC layer can be easily achieved. From the same perspective, the ratio is more preferably 0.03 or less, and further preferably 0.02 or less.
[0109] In addition, when the ratio is 0.005 or more, the excellent alkali diffusion prevention function of the SiOC layer can be exerted, and the layer peeling on the glass substrate can be easily suppressed when the glass article is formed at a high temperature. From the same point of view, the ratio is more preferably 0.008 or more, and further preferably 0.010 or more.
[0110] Thickness of shielding layer t sh The thickness can be appropriately set, but is preferably 8 μm or more and 20 μm or less, and more preferably 10 μm or more and 15 μm or less, from the viewpoint of excellent light resistance and concealment of the exposed adhesive.
[0111] <Method for manufacturing glass article>
[0112] The production method of the present glass article is not particularly limited, and the glass article can be produced, for example, by a production method including the following steps.
[0113] A step of preparing a glass substrate (substrate preparation step).
[0114] A step of forming a SiOC layer on a glass substrate (SiOC layer forming step).
[0115] A step of forming a TCO layer on the SiOC layer (TCO layer forming step).
[0116] A step of forming a shielding layer on the TCO layer (shielding layer forming step).
[0117] The substrate preparation step (substrate production step) may include a step of melting glass raw material and pouring the melted glass raw material into a tin bath (melting step), and a step of annealing the melted glass raw material (annealing step).
[0118] The TCO layer forming step may include, for example, the following steps.
[0119] A step of forming a first TCO layer on the SiOC layer (first TCO layer forming step).
[0120] A step of forming a second TCO layer on the first TCO layer (a step of forming a second TCO layer).
[0121] The shielding layer forming step may include, for example, the following steps.
[0122] A step of preparing a material for forming a shielding layer (a step of preparing a material for forming a shielding layer).
[0123] A step of coating the shielding layer forming material on the TCO layer (coating step).
[0124] A step of sintering the shielding layer forming material applied on the TCO layer (sintering step).
[0125] The above-mentioned manufacturing method may further include the following steps.
[0126] A step of heat-forming the glass substrate on which the SiOC layer, the TCO layer, and the shielding layer are sequentially arranged into a desired shape (heat-forming step).
[0127] A step of cooling the heat-formed glass substrate (cooling step).
[0128] These steps may be performed sequentially, or multiple steps (such as a substrate preparation step (specifically a melting step), a SiOC layer forming step, a shielding layer forming step (specifically a sintering step), and a heating and forming step) may be performed simultaneously.
[0129] The above-mentioned manufacturing method will be described in detail below.
[0130] First, prepare, for example, a rectangular glass substrate (glass plate) (substrate preparation process). At this time, the glass substrate can be purchased and used as a commercial product, or it can be made, for example, by the following method. That is, the glass raw materials formulated into the desired glass composition are heated at a specified temperature to obtain molten glass. Next, the obtained molten glass is flowed into a tin bath filled with molten tin (melting process), formed into a plate-shaped glass ribbon, and annealed (annealing process) to obtain a glass substrate. At this time, the obtained glass ribbon can also be subjected to processing treatment (for example, SO2 treatment or cleaning treatment). In addition, the forming of the glass substrate can be carried out in any of the above-mentioned melting process and annealing process. In addition, when making the glass substrate, it can be appropriately cut to the desired size.
[0131] Next, a SiOC layer is formed on at least a portion of one surface of the glass substrate, for example, on the entire surface of one surface of the glass substrate (SiOC layer forming process). As described above, the SiOC layer is preferably manufactured using an online CVD method, which forms a film directly on a glass substrate on a float line. Specifically, the SiOC layer is formed by spraying a mixed raw material gas at normal pressure (1013hPa) on a glass substrate heated to a specified temperature. At this time, a mixed gas of silane gas, ethylene gas, carbon dioxide gas and nitrogen gas can be used as the raw material gas. The composition of the SiOC layer produced can be adjusted by changing the combination of the raw material gas, etc. In addition, the formation of the SiOC layer using the online CVD method can be carried out simultaneously with the melting process when the glass substrate is produced. That is, in the above-mentioned melting process, the SiOC layer can also be formed by spraying the above-mentioned raw material gas on the glass surface of the molten glass flowing into the tin bath. Thereby, the layer formation performed by the online CVD method can be carried out simultaneously with the production process of the glass substrate.
[0132] Then, a TCO layer is formed on at least a portion of the SiOC layer, for example, on the entire surface of the SiOC layer (TCO layer forming process). At this time, when the TCO layer is composed of two or more layers, these layers are formed in sequence. For example, when the TCO layer is composed of a first TCO layer and a second TCO layer, after the first TCO layer is formed on the SiOC layer (first TCO layer forming process), the second TCO layer is formed on the first TCO layer (second TCO layer forming process). As described above, the TCO layer is preferably continuously produced after the SiOC layer is formed on the glass substrate using an online CVD method. Specifically, the TCO layer is formed by spraying a mixed raw material gas at normal pressure on a glass substrate formed with a SiOC layer heated to a specified temperature. At this time, when a Sb:SnOx layer is produced as a TCO layer, a mixed gas composed of a MBTC (monobutyltin trichloride) raw material, a Sb raw material, HCl gas and NHO3 gas can be used as the raw material gas. When a F:SnOx layer is produced as a TCO layer, a mixed gas consisting of an MBTC raw material, a F raw material (trifluoroacetic acid (TFA)), oxygen and nitrogen can be used as a raw material gas. The composition of the produced TCO layer can be adjusted by changing the raw material gas formulation.
[0133] Subsequently, a frame-shaped shielding layer is formed on at least a portion of the TCO layer (the outermost TCO layer when the TCO layer is composed of multiple layers), for example, on the peripheral portion of the TCO layer (shielding layer forming step). Specifically, a shielding layer forming material (for example, a ceramic color paste) is applied to at least a portion of the glass substrate on which the SiOC layer and the TCO layer are formed (coating step), and dried as needed. There is no particular limitation on the method for applying the shielding layer forming material, and for example, a screen printing method or an inkjet method can be used. Specifically, it is preferably printed on the glass substrate using a #150 to #250 mesh screen.
[0134] The shielding layer forming material may be a commercially available product or may be prepared separately (shielding layer forming material preparation step). The shielding layer forming material may be prepared, for example, by dispersing the above-mentioned necessary glass frit and pigment in an organic vehicle.
[0135] Next, the obtained glass substrate is heated to a predetermined temperature using a firing furnace such as an IR furnace, and the shielding layer forming material is sintered on the glass substrate (sintering process). The heating (firing) temperature is not particularly limited, and is preferably 550 to 730°C. The firing speed (transport speed) is also not particularly limited, and is preferably 5 to 30 mm / s. By changing these firing conditions, the crystallinity value of the produced shielding layer can be adjusted. Through the above process, a shielding layer is formed on the glass substrate.
[0136] Then, the glass substrate on which the SiOC layer, the TCO layer and the shielding layer are sequentially arranged is heated and formed into a desired shape (heating and forming step), and a cooling operation is performed as needed (cooling step). In addition, the glass substrate may be bent by its own weight or pressurized while being kept at the heating temperature in the sintering step to form it into a desired shape. That is, the heating and forming step and the sintering step may be performed simultaneously.
[0137] In press bending, for example, a glass plate is bent using a pressurizing device (heating and pressing device) according to the desired shape of the automobile window glass. In self-weight bending, the glass substrate is bent using a self-weight bending device. Furthermore, air cooling and strengthening may be performed in accordance with the safety standards required for automobile window glass.
[0138] The glass article obtained by the above process has excellent heat resistance and can suppress the peeling and cracking of each layer on the glass substrate. In addition, the glass article does not use whisker-shaped refractory materials, and can have both the low-temperature sintering property of the shielding layer forming material and the high plate strength of the glass article.
[0139] Example
[0140] The present invention will be described in more detail below using a plurality of examples, but the present invention is not limited to these examples. Examples 1 to 3 are examples of the present glass article, and Examples 4 to 6 are comparative examples.
[0141] [Example 1]
[0142] (Example 1-1) Preparation of glass substrate
[0143] Glass raw materials SiO2, Al2O3, MgO, CaO, Na2O and K2O are heated at a temperature of 1450-1700°C to obtain molten glass. Next, the molten glass is flowed into a tin bath filled with molten tin and formed into a plate-shaped glass ribbon. At this time, the tin bath is a mixed gas atmosphere of H2 and N2, and the temperature is 950-1200°C on the upstream side and 500-950°C on the downstream side. Subsequently, the obtained glass ribbon is annealed, and at this time, SO2 treatment is simultaneously implemented in the annealing furnace. Specifically, a mixed gas of SO2 gas and air is sprayed from the bottom surface (the surface in contact with the tin bath) of the glass ribbon. Then, after the SO2 treatment, the obtained glass ribbon is washed with a mixture of calcium carbonate and water and a mixture of neutral detergent and water, respectively, to remove the protective layer of sulfate attached to both sides of the glass ribbon. In this way, a glass substrate is obtained. The thickness of the glass substrate is 2.1 mm. The composition of the produced glass substrate is shown in Table 2 below. Here, since the composition near the surface of the glass substrate is generally unstable, the blending amount of each component described in Table 2 is expressed as a mass percentage based on oxides at a depth of approximately 5000 nm from the surface of the glass substrate where the composition is stable.
[0144] Table 2
[0145] Composition Compounding amount (%) <![CDATA[SiO2]]> 71.4 <![CDATA[Al2O3]]> 1.1 MgO 5.5 CaO 7.8 <![CDATA[Na2O]]> 13.6 <![CDATA[K2O]]> 0.4 The rest (impurities) 0.2
[0146] (Example 1-2) Preparation of SiOC layer and TCO layer
[0147] On one surface of the glass substrate, a SiOC layer, a first TCO layer and a second TCO layer are continuously formed by an online CVD device. Specifically, a mixed gas consisting of the following raw material gases is sprayed at atmospheric pressure on one surface of a glass substrate heated to 600-1100° C. under the following SiOC layer film forming conditions to form a SiOC layer with the following thickness.
[0148] SiOC layer film forming conditions
[0149] Raw gas: silane gas (0.585 kg / hr), ethylene gas (2.03 kg / hr), carbon dioxide (6.10 kg / hr), nitrogen (4.30 kg / hr).
[0150] Glass substrate temperature: 600~1100℃.
[0151] Film forming pressure: normal pressure.
[0152] The film thickness of the SiOC layer is 80 nm.
[0153] Next, a mixed gas composed of the following raw materials was sprayed at atmospheric pressure on the surface of the SiOC layer heated to 600-1100° C. under the following first TCO layer formation conditions to form a first TCO layer (SnOx:Sb) with the following thickness.
[0154] ·First TCO layer film forming conditions
[0155] Raw materials: MBTC raw material (37.3 L / hr), Sb raw material (6.0 volume %: ratio when MBTC raw material is 100 volume %), HCl gas (7.17 kg / hr), NHO3 gas (38.9 L / hr).
[0156] Glass substrate temperature: 600~1100℃.
[0157] Film forming pressure: normal pressure.
[0158] Film thickness: 430nm.
[0159] Then, a mixed gas composed of the following raw materials was sprayed at normal pressure on the entire surface of the first TCO layer heated to 600-1100° C. under the following second TCO layer formation conditions to form a second TCO layer (SnOx:F) with the following thickness.
[0160] · Second TCO layer film forming conditions
[0161] Raw materials: MBTC raw material (18.18 L / hr), F raw material (TFA) (7.08 L / hr), oxygen (24.43 Nm3 / hr), nitrogen (20.28 Nm 3 / hr).
[0162] Glass substrate temperature: 600~1100℃.
[0163] Film forming pressure: normal pressure.
[0164] Film thickness: 200nm.
[0165] (Example 1-3) Production of shielding layer
[0166] On the glass substrate, specifically on the periphery of the second TCO layer, a shielding layer is formed that includes Bi4(SiO4)3 as a crystalline component in the XRD measurement data and CuCrMnO spinel pigment as a pigment. Specifically, a commercially available shielding layer forming material (trade name: 14501, manufactured by Ferro) is printed on the periphery of the second TCO layer using a #150 to #250 mesh screen printing method and dried. Next, the shielding layer forming material is sintered on the glass substrate using a sintering furnace (IR furnace) under the following sintering conditions to form a Figure 1B The frame-shaped shielding layer shown.
[0167] Firing conditions
[0168] Firing temperature: 680~710℃
[0169] Firing speed (conveying speed): 5~30mm / s.
[0170] The thickness of the shielding layer is 15 μm. Through the above steps, a glass substrate having a SiOC layer, a TCO layer and a shielding layer stacked thereon can be obtained.
[0171] <Evaluation Method>
[0172] The glass substrate prepared in Example 1 was evaluated by the following evaluation method.
[0173] [Heat resistance evaluation (film peeling and crack generation evaluation)]
[0174] In Example 1, while the shielding layer was sintered on the glass substrate at 680-710°C, it was simultaneously subjected to press bending to produce a curved automobile window glass. The obtained automobile window glass was placed in a high temperature and high humidity tank (temperature 80°C or higher, relative humidity 95% or higher), and the presence of film peeling and cracking was visually confirmed every 24 hours, and evaluated according to the following evaluation criteria. The evaluation results are shown in Table 3 described below.
[0175] Evaluation criteria
[0176] 4: No peeling or cracking occurred even after 2000 hours.
[0177] 3: No peeling or cracking occurred after 1500 hours, but peeling and / or cracking occurred between 1500 and 2000 hours.
[0178] 2: No peeling or cracking occurred after 1000 hours, but peeling and / or cracking occurred between 1000 and 1500 hours.
[0179] 1: Peeling and / or cracking occurred before 1000 hours.
[0180] <Measurement methods of physical properties>
[0181] The methods for measuring the physical properties of the glass substrate are as follows.
[0182] [Linear expansion coefficient]
[0183] The linear expansion coefficients of the glass substrate and the layers stacked on the glass substrate (here, the shielding layer) were measured by the following method. That is, the thermal expansion curve of the object to be measured cut into a predetermined shape (e.g., a 5 cm rod) was measured in the temperature range of 25 to 300°C using an Orton dilatometer, and the linear expansion coefficient was calculated based on these data. The measurement results for the shielding layer are shown in Table 3 described below. The α of the SiOC layer in Example 1 is Si In the range of 0.6~4.0×10 -6 / K range.
[0184] [C / Si]
[0185] The element ratio of the SiOC layer was measured by ESCA (Electron Spectroscopy Chemical Analysis). The device was manufactured by ULVAC-PHI (アルバック·ファイ) and used a scanning X-ray photoelectron spectrometer (XPS) PHI Quantera II (trade name). The sample was cut into a size that could be accommodated on the data table of the measuring device (several millimeters square), and the sample was set in the device. Input the measuring conditions (analysis diameter: 100μmφ, X-ray setting (X-ray setting): 25W, 15kv, sputtering setting (Sputter setting): 2kv (2mm×2mm area), vacuum during analysis: about 2×10 -7Pa), and repeatedly measured while filming with a sputtering gun (for film cutting), thereby performing composition analysis in the film. The film composition in the SiOC layer was analyzed, and the C / Si value was calculated using the element ratio in the central part of the SiOC layer. The calculated values are shown in Table 3.
[0186] [Crystallinity value]
[0187] The crystallinity of the shielding layer is calculated by XRD (X-ray Diffraction). The device is manufactured by Rigaku Co., Ltd. and uses a fully automatic multi-purpose X-ray diffraction device Smart Lab (trade name). The measurement sample is cut into a size that can be accommodated on the data table of the measurement device (several centimeters square), and the sample is set in the device. Input the measurement conditions (tube voltage 45kV, tube current 200mA), and use the 2θ / θ scanning method to measure at a measurement angle of 10 degrees to 80 degrees, a step of 0.02 degrees, and a scanning speed of 20 degrees / minute. Using the obtained x-axis 2θ / θ angle and y-axis CPS (Count Per Second) values, the crystallinity value of the shielding layer (CPS of Bi4(SiO4)3 crystalline phase / CPS of Cu-Cr-Mn-O spinel pigment phase) is calculated. The calculated crystallinity values are shown in Table 3. The peak of the Bi4(SiO4)3 crystal phase was 2θ / θ: 32.6 degrees, and the peak of the Cu-Cr-Mn-O spinel pigment phase was 2θ / θ: 35.8 degrees. In Examples 5 and 6 described below, the crystallinity value was not measured.
[0188] [(C / Si) / crystallinity value]
[0189] The calculated values are shown in Table 3.
[0190] [Example 2]
[0191] A glass substrate having various layers was prepared in the same manner as in Example 1 except that the firing conditions of the shielding film forming material in the firing furnace were changed as follows, and evaluation was performed according to the above-mentioned evaluation method to measure various physical property values.
[0192] Firing conditions
[0193] Firing temperature: 680℃,
[0194] Firing speed: 10mm / s.
[0195] The α of the SiOC layer in Example 2 Si In the range of 0.6~4.0×10 -6 / K range.
[0196] [Example 3]
[0197] A glass substrate having various layers was prepared in the same manner as in Example 1 except for the following changes, and the evaluation was performed according to the above evaluation method to measure the various physical property values. Specifically, in Example 3, the raw material gas used in the film forming conditions of the SiOC layer and the firing conditions of the material for forming the shielding film in the firing furnace were changed as follows.
[0198] SiOC layer film forming conditions
[0199] Raw material gases: silane gas (0.335 kg / hr), ethylene gas (0.64 kg / hr), carbon dioxide gas (14.11 kg / hr), and nitrogen gas (1.00 kg / hr).
[0200] Firing conditions
[0201] Firing temperature: 710℃
[0202] Firing speed: 25mm / s.
[0203] The α of the SiOC layer in Example 3 Si In the range of 0.6~4.0×10 -6 / K range.
[0204] [Example 4]
[0205] A substrate having each layer was prepared in the same manner as in Example 1 except that the raw material gases used in the SiOC layer formation conditions, the first TCO layer formation conditions, and the second TCO layer formation conditions were changed as follows, and evaluation was performed according to the above-mentioned evaluation method to measure various physical property values.
[0206] SiOC layer film forming conditions
[0207] Raw material gases: silane gas (0.335 kg / hr), ethylene gas (0.64 kg / hr), carbon dioxide gas (14.11 kg / hr), and nitrogen gas (1.00 kg / hr).
[0208] ·First TCO layer film forming conditions
[0209] Raw materials: MBTC raw material (50.6 L / hr), Sb raw material (6.0%), HCl gas (9.37 kg / hr).
[0210] ·Second TCO layer film forming conditions
[0211] Raw materials: MBTC raw material (17.93 L / hr), F raw material (TFA) (6.98 L / hr), oxygen (24.10 Nm 3 / hr), nitrogen (20.28Nm 3 / hr).
[0212] [Example 5]
[0213] A glass substrate having various layers was prepared in the same manner as in Example 1 except for the following changes, and the evaluation was performed according to the above evaluation method to measure the values of various physical properties. Si In the range of 0.6~4.0×10 -6 Specifically, in Example 5, the shielding layer forming material used in Example 1 was changed to a product name: B9-71, manufactured by Ferro Corporation.
[0214] [Example 6]
[0215] A glass substrate having various layers was prepared in the same manner as in Example 1 except for the following changes, and the evaluation was performed according to the above evaluation method to measure the various physical property values. Specifically, in Example 6, the raw material gas used for the film formation conditions of the SiOC layer was changed to silane gas (0.335 kg / hr), ethylene gas (0.64 kg / hr), carbon dioxide gas (14.11 kg / hr), and nitrogen gas (1.00 kg / hr). In addition, in Example 6, the shielding layer forming material used in Example 1 was changed to the trade name: B9-83, manufactured by Ferro Corporation.
[0216] α of the SiOC layer in Example 6 Si In the range of 0.6~4.0×10 -6 / K range.
[0217] Table 3 shows the measurement results of the SiOC layer and the shielding layer of each example and the evaluation results evaluated by the above-mentioned evaluation method.
[0218]
Table 3
[0219]
[0220] As shown in Table 3 above, the C / Si of the SiOC layer is 0.1 to 0.5 and the α sh 7.7×10 -3 The present glass article having a value of φ / K or less exhibits excellent heat resistance. Furthermore, the present glass articles obtained in Examples 1 to 3 also have excellent mold releasability.
[0221] This application claims the benefit of priority based on Japanese patent application No. 2020-149056, filed on September 4, 2020, the disclosure of which is incorporated herein in its entirety.
[0222] Explanation of symbols
[0223] 1 Glass substrate
[0224] 2 Adding carbon silicon oxide layer (SiOC layer)
[0225] 3 Transparent Conductive Oxide Layer (TCO Layer)
[0226] 3a First TCO layer
[0227] 3b Second TCO layer
[0228] 4 Shielding layer.
Claims
1. A glass article, comprising a carbon-added silicon oxide layer, a transparent conductive oxide layer and a shielding layer in this order on a glass substrate, wherein the ratio of the atomic composition percentage of carbon to silicon in the carbon-added silicon oxide layer (C / Si) is greater than or equal to 0.1 and less than or equal to 0.5, and the linear expansion coefficient α of the shielding layer is Sh At 7.7×10 -3 / K or less, the shielding layer includes a crystalline component and a pigment, and a crystallinity value represented by a CPS ratio of the crystalline component to the pigment in X-ray diffraction measurement data of the shielding layer is 7 or more and 33 or less.
2. A glass article, comprising a carbon-added silicon oxide layer, a transparent conductive oxide layer and a shielding layer in this order on a glass substrate, wherein the ratio of the atomic composition percentage of carbon to silicon in the carbon-added silicon oxide layer (C / Si) is greater than or equal to 0.1 and less than or equal to 0.5, and the linear expansion coefficient α of the shielding layer is Sh At 7.7×10 -3 / K or less, the shielding layer contains a crystalline component and a pigment, and the C / Si ratio of the carbon-added silicon oxide layer to the crystallinity value represented by the CPS ratio of the crystalline component to the pigment in the X-ray diffraction measurement data of the shielding layer is greater than 0.005 and less than 0.
04.
3. The glass article according to claim 1 or 2, wherein: The linear expansion coefficient of the carbon-added silicon oxide layer is α Si At 0.6×10 -6 / K or above and 4.0×10 -6 / K or less.
4. The glass article according to claim 3, wherein: The linear expansion coefficient of the carbon-added silicon oxide layer is α Si In 2.9×10 -6 / K or less.
5. The glass article according to claim 1 or 2, wherein: The thickness t of the glass substrate g It is not less than 2.0 mm and not more than 3.5 mm.
6. The glass article according to claim 1 or 2, wherein: The thickness of the carbon-added silicon oxide layer is t Si It is greater than or equal to 30 nm and less than or equal to 150 nm.
7. The glass article according to claim 1 or 2, wherein: The transparent conductive oxide layer includes at least one of a fluorine-doped tin oxide layer and an antimony-doped tin oxide layer.
8. The glass article according to claim 1 or 2, wherein: It is used as window glass for automobiles.
Citation Information
Patent Citations
Modified black spinel pigments for glass and ceramic enamel applications
JP2019509959A
Vehicle Glazing
JP2019533630A
Display device
JP2020149056A
Vehicle glazing
CN109983839A
Ceramic ink jet printing ink for low-expansion glass and / or low-expansion glass-ceramic and use thereof
EP3169735A1